THE ROLE OF HISTORY IN THE EDUCATION SYSTEM IN CENTRAL ASIA: A BRIEF RETROSPECTIVE LOOK (BEFORE 1917) - Ra’no Kodirova (Sciental Journals Publishing, 2025)
The article examines the role of the subject of history in the education system in Central Asia in the Middle Ages and modern times. Based on an analysis of sources and literature, the authors hypothesize that history was not taught as an academic discipline in old religious maktabs (schools) and madrasahs. It is argued that for the first time, as a separate subject, history began to be studied by students of educational institutions created in Turkestan by the Russian colonial authorities—parish, city, and Russian-native schools and gymnasiums. In the national education system, history was included for the first time in the curricula of the new method schools opened by the Jadids. The article presents thoughts on the problems of teaching history in schools and madrasas in Turkestan in the late 19th and early 20th centuries, the subjects and books taught in them, and, in particular, the subject of history.
Keywords: Educational institution, old school , madrasah, parochial schools, city schools, Russian-native schools, gymnasium, new method schools, history as an academic discipline, general history, national history, local history, curriculum, textbook, chrestomathy, class-lesson system, verbal method, laboratory method, method of preparing essays.